Conventional Surgery in the Management of Denture Induced Fibrous Hyperplasia - ACase report. (2020) - Bouguezzi, Adel; Chagra, Jade; Chokri, Abdellatif; Omami, Mounir; Sioud, Sameh; Hentati, Hajer; Selmi, Jamil
No abstract available